Teoria do terceiro cúmplice no inadimplemento contratual : fundamento e elementos de aplicação - Ruas, Celiana Diehl (2017)
This dissertation investigates whether a third party totally foreign to the contractual relationship can be held accountable to the creditor for interfering in such relationship and induce the debtor to breach of contract. For this purpose, it begins with the distinction between parties and third parties, followed by the study of the origin, development and current configuration of privity of contract, in order to verify if it is an obstacle to the third party's liability. It examined the tort of interference with contractual relations in England and United States law, as well as the notion of opposability of the contract, the social function of contracts, the good faith principle and the abuse of rights theory, which are the main foundations invoked in civil law system to support the accountability of the third party. It was found that the extremely closed conception of privity of contracts, as a dogma that kept contract in a true isolation, was overtaken by a jurisprudential and doctrinal rereading. Privity of contract remains valid and expresses the notion that the binding effects of the contract are, as a rule, restricted to the parties, but coexists with the idea that the contract must be respected by third parties who are aware of it, based on the general opposition of subjective rights. Having established the possibility and the basis for the third party's liability, it was necessary to establish the guidelines for its application, which was based on an analysis of the third party's civil liability characteristics, as well as the general and specific requisites for its configuration. The applicable sanction was examined in order to establish whether indemnification or recomposition of the creditor's right is preferable. The applicability to the third party of any penal clause contained in the agreement entered into between creditor and debtor has been subject of examination, as such this question could give rise to relevant theoretical and practical problems. Finally, the analysis of national jurisprudence on the subject indicated that the doctrine of the third party complies with jurisprudence, although the basis indicated in the decisions is mostly incorrect.